Predicting sexual intention to engage in premarital sex among late adolescent in Kuantan government secondary schools: an application of theory of planned behaviour - Abdullah, Fa’iza; Draman, Samsul; Abd. Aziz, Karimah Hanim; Zainuddin, Nurul Akmanidar; Muhammad, Noor Azimah (International Medical Journal Malaysia, 2020)
Introduction: Based on the Theory of Planned Behaviour (TPB), sexual intention is determined by three main socio-cognitive factors which are permissive attitudes, social-norms and self-efficacy in performing premarital sexual activity. Premarital sex associated with increased risk of sexually transmitted diseases and detrimental social implications. The aim of this study was to explore the correlation of the socio-cognitive factors in predicting intention to engage in premarital sex amongst late adolescents in Kuantan government secondary schools. Method: This cross-sectional study was conducted among 466 pre-university students aged 18-19 years from nine government secondary schools in Kuantan district. A self-administered validated Youth Sexual Intention Questionnaire (YSI-Q) was used. Statistical analyses were done using IBM SPSS version 22.0. Results: Permissive attitude (r=0.579, p<0.001), perception of social-norms (r=0.513, p<0.001) and perceived self-efficacy (r=0.253, p<0.001) were positively correlated with the sexual intention towards premarital sex. The higher the permissive attitude, social-norms and perceived self-efficacy, the higher the sexual intention score. There was a significant difference in the level of sexual intention between male (35.6%) and female (64.4%) with mean (SD) score of 10.54 (3.8) and 7.3 (2.9) respectively. Students with premarital sex experience (1.5%) showed significantly higher score in sexual intention than student without premarital sex experience (t=4.54, p<0.001). Conclusion: This study confirmed permissive attitude, perception of social-norms and perceived self-efficacy were positively correlated with sexual intention towards premarital sex among the late adolescents. Therefore, it is important to consider this TPB theoretical framework in designing sexual abstinence intervention to curb the unsafe sexual behaviour.